PENGEMBANGAN E-MODUL FIFIKA TERINTEGRASI STEM UNTUK MENDORONG KETERAMPILAN BERPIKIR KRITIS DAN KREATIF SISWA - Yonira Mike Vindi Marta; Asrizal; Ramli (Jurnal Penelitian Pendidikan IPA, 2025)
Twenty first century learning requires students to have critical thinking skills, creative thinking, communication, and collaboration. The learning outcomes show that students' independence is very lacking and students' critical and creative thinking skills are low. This development aims to produce a product in the form of an e-module physics class XI senior high school integrated with the STEM approach with critical and creative thinking skills as a solution to this problem. The purpose of this study was to determine the initial studies, the validity, and practicality of using STEM-integrated e-modules. The development model used is the ADDIE development model. The data analysis technique used is descriptive statistics. Based on the data that has been analyzed there are three research results. First, at the analysis stage, an analysis of learning activities is carried out, student needs analysis, and educator interviews. Second, the validation result is 0.82 with a valid category. Third, the result of practicality by students is 79.5 and the result of practicality by educators is 87.5 with practical and very practical categories. The results of this study imply that students become more active and creative because of STEM activities. The results of the study concluded that the STEM approach integrated physics e-module is valid and practical for use in learning.